Morphological and molecular variability in Fusarium solani causing wilt of patchouli - CHAVAN, SREEDEVI S.; HEGDE*, YASHODA R.; PRASHANTHI, S.K. (Indian Phytopathology, 2011)
Eight isolates of Fusarium solani collected from different parts of Karnataka were used to study the morphologicaland molecular variability. The maximum colony diameter was observed in isolate Fs1 (90mm) whereas minimum colonydiameter was observed in isolate Fs7 (84mm). Sporulation was abundant in isolates Fs1, Fs2 and Fs4. The size of macroconidiaand microconidia was maximum in isolate Fs8. PCR amplification of total genomic DNA with 20 primers generated uniquebanding patterns depending upon primers and isolates. Polymorphism per primer ranged from 50 (OPB 3) to 100 per cent withOPA 3, OPA 4, OPA 7, OPA 10, OPA 11, OPA 15 and OPB 4 primers. The dendrogram of different isolates resulted in two majorclusters A and B at similarity coefficient of 0.71.